2013
DOI: 10.1093/fampra/cmt033
|View full text |Cite
|
Sign up to set email alerts
|

Most common diseases diagnosed in primary care in Stockholm, Sweden, in 2011

Abstract: The 30 most common diagnoses in primary care reflect the complexity of disorders cared for in the first line of health care. Knowledge of these patterns is important when aiming at using primary health care resources in a proper way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 25 publications
8
76
0
5
Order By: Relevance
“…In terms of reported medical diagnosis, diseases of the Cardiovascular System (Hypertension), the Endocrine System (Type 2 Diabetes Mellitus and Hypothyroidism) and Infectious (Cold/Flu) and Osteoarticular diseases (chronic joint pain) were the most prevalent, data that reinforces the findings of other studies 16,17 . These conditions require constant monitoring by health teams and proper monitoring and control, as well as the regular dispensing of medications.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of reported medical diagnosis, diseases of the Cardiovascular System (Hypertension), the Endocrine System (Type 2 Diabetes Mellitus and Hypothyroidism) and Infectious (Cold/Flu) and Osteoarticular diseases (chronic joint pain) were the most prevalent, data that reinforces the findings of other studies 16,17 . These conditions require constant monitoring by health teams and proper monitoring and control, as well as the regular dispensing of medications.…”
Section: Discussionsupporting
confidence: 85%
“…In a review of cross-sectional data from Sweden, tonsillitis was observed in 2.36% of the collective pediatric and adult population studied. Of these diagnoses, 45.4% of cases occurred in children ages 17 and under; after data extrapolation 3.43% of all pediatric visits had the principal diagnoses of tonsillitis [13]. Additionally, a study of Norwegian children between the ages of four and five found that 6.9% of children had experienced more than one episode of 'tonsillopharyngitis' in the past year [14].…”
Section: Discussionmentioning
confidence: 99%
“…All contacts with all health care providers and the corresponding diagnoses for each visit are stored in VAL, with the exception of those for a few private clinics that operate without subsidies in the Stockholm area. 24 VAL has coverage of more than 99% of hospital care in the county. 24 The number of patient visits to the ED each hour for hospital B for the study timeframe was collected from AkuSys.…”
Section: Study Setting and Selection Of Participantsmentioning
confidence: 99%
“…24 VAL has coverage of more than 99% of hospital care in the county. 24 The number of patient visits to the ED each hour for hospital B for the study timeframe was collected from AkuSys. The number of patient visits to the EDs each day for hospitals A, C, D, E, and F for the study timeframe was collected from the VAL database.…”
Section: Study Setting and Selection Of Participantsmentioning
confidence: 99%